Effect of cutting height on agronomic parameters of Tithonia diversifolia - Canto Saenz, Francys Mitchel (2023)
The agronomic parameters of Tithonia diversifolia were evaluated by the effect of four cutting heights (AC) from the ground (AC1: 0 cm, AC2: 10 cm, AC3: 20 cm, AC4: 30 cm); with four replicates each, by 55 days. Shoots/tiller, leaves/shoot and leaves/tiller were higher (p<0.05) in AC1. However, the number of leaves/bush and shoots/bush were higher (p<0.05) in AC2, AC3 and AC4. The green forage weight (FV)/tiller was higher (p<0.05) in AC1; although, the weight of FV/mat was higher in AC2, AC3 and AC4, showing a higher (p<0.05) yield (kg/m2) in FV and dry matter for AC2, AC3 and AC4. The higher number of leaves/shoot (p<0.05) in AC2 than AC4 could improve the productivity of T. diversifolia, suggesting AC2 as adequate AC.